(untitled) (Journal of Hama University, 2024)
This study examines the impact of outsourcing motives on the level of outsourcing in Non-Profit Organizations (NPOs). The study aims to analyze how different outsourcing motives influence the extent to which NPOs engage in outsourcing activities. Through a comprehensive literature review, various outsourcing motives were identified. The research also explores different types of outsourcing arrangements, including one-time contracts, periodic contracts, long-term project contracts, and multiple services contracts. Data was collected from Aga khan Institution to assess the extent of their outsourcing activities and the underlying motives driving such decisions. The findings shed light on the significant impact of outsourcing motives on the level of outsourcing in Aga khan Institution. Cost reduction and access to expertise emerge as key drivers for outsourcing decisions, with organizations utilizing outsourcing to optimize their financial resources and leverage external specialized knowledge. Moreover, the study highlights that NPOs’ outsourcing decisions are influenced by a combination of motives rather than a single factor. In conclusion, this study contributes to the understanding of outsourcing practices within Aga khan Institution and emphasizes the importance of considering various motives when making outsourcing decisions. It provides insights for Aga khan Institution managers and decision makers to enhance the efficiency and effectiveness of outsourcing strategies, ultimately supporting their missions and objectives.